Từ chiều sâu giao tiếp ngôn ngữ - Nguyễn, Lai (Hà Nội, 2013)
President Ho Chi Minh was not a linguist. He always used the language and guided people to use it with highest efficiency only for the sake of the revolution. In this article, the author studies the contribution of President Ho's language usage in the aspect of his very creative semantis formation in the dynamism of his efficient language communication which was not neutral, but oriented the people, taking the people's language, knowledge and perception ability as a basis for language communication.